ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP PERMINTAAN CABAI MERAH - Eva Lusiana; Yuhanin Zamrodah; Tri Kurniastuti; Luhur Aditya Prayudi (grafting, 2022)
This study aims to determine the characteristics of red chili consumers in Blitar Regency with criteria: based on age, gender, education, occupation, income, number of family members, price of red chili. The purpose of the next study is to find out how psychological, personal, social, and cultural factors are based on consumers' decisions in making demand for red chili. The research uses descriptive qualitative methods and quantitative methods. The population used is consumers who have made requests for red chili peppers and the technique used is Non Probabilitiy sampling with the Side Purposivve method. The results showed that independent variables showed that they were valid and reliable and had passed the classical assumption test. Furthermore, social variables have a significant effect on the demand for red pepper. Furthermore, psychological, social, and cultural variables have a significant simultaneous effect on the demand for red pepper.